Urbanization, Land Scarcity and Urban Farmers' Mobility: Evidence from Ghana - Michael Tuffour (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
This study assessed how urban farmers survive land scarcity challenges in the midst of rapid urbanization in a developing country such as Ghana. As land scarcity becomes more pronounced in urban areas, farmers struggle to find a place to farm within the urban space but the numerous opportunities that come with farming within the city still inspires them to find spare lands and open spaces in the city to farm. Therefore, the study examined the factors that influence urban farmers’ mobility with respect to farmland in the midst of intense land scarcity. Reponses from 251 farmers were analyzed with both Tobit and Ordinary Least Squares (OLS). Land situation factors such as land ownership type, land scarcity challenges, and size of land were found to be associated with farmers’ mobility. Farm characteristics such as level of market benefits, intensity of vegetable production, and level of technology were also associated with farmers’ mobility within the city. Personal characteristics such as age, level of education, level of farmer engagement, and marital status also played a role. This implies urban farming sustainability requires conscious government efforts to include urban agriculture in its spatial planning decisions since there are numerous opportunities for farming within the city.